Pengembangan Sumber Daya Aparatur Sipil Negara Pada Badan Kepegawaian Dan Pengembangan Sumber Daya Manusia Provinsi Sulawesi Tenggara - Alwan, Alwan; Mustafa, La Ode; Elwan, La Ode Muhammad (REZ PUBLICA, 2021)
This study aims to identify and describe the development of state civil servants in the Southeast Sulawesi Province Civil Service and Human Resources Development Agency to identify and describe the performance of civil servants in the Southeast Sulawesi Province Civil Service and Human Resources Development Agency. The method used in this research is qualitative descriptive research method, with data collection techniques carried out by using the method of observation, interviews and documentation. The results of this study indicate that the Development of State Civil Apparatus Resources in the Personnel and Human Resources Development Agency of Southeast Sulawesi Province has improved, it can be seen that education to occupy positions in organizations is given to him to advance to a higher and better level and training. what has been done has helped employees understand practical knowledge and its application, And the performance of State Civil Service Employees is enough to carry out their work well because Civil Servants can serve the community well, but are friendly, but sometimes there are employees who do not understand their work and also the timeliness or discipline where there are still employees who come late and even a leader rarely comes to the office.